Agro-Nutrition: The role of orange-fleshed sweetpotato in building resilient refugee communities in South-Western Uganda - International Potato Center (2024)
As of 2024, the global refugee population has surged to 43.4 million, a significant increase from 41 million in 2010! Uganda, now hosting over 1.74 million refugees, has emerged as Africa’s largest and the world’s fifth-largest refugee host nation. This influx has placed immense strain on the country’s resources, with refugees facing constant vulnerability and heavy reliance on humanitarian aid. To mitigate this dependency, Uganda has shifted its focus towards promoting self-reliance among refugees. This strategic shift has been catalysed by the gradual reduction in food aid and resources. To support this transition, the United Nations High Commissioner for Refugees (UNHCR) and the World Food Programme (WFP) established a hub to coordinate aid efforts among various agencies and NGOs. In 2019-2020, the International Potato Center (CIP) and WFP, in collaboration with other partners, initiated an agro-nutrition pilot project. Recognizing the strong link between food insecurity and poor diets, the project aimed to improve the nutritional status of refugee communities and school children by promoting the cultivation of Vitamin A-rich, orange-fleshed sweetpotato (OFSP) within schools and refugee communities. The success of this pilot has led to the integration of OFSP into Uganda’s self-reliance model across South-Western Uganda in 2024. A 2023 UNICEF report highlights the significant nutritional gap, with only 17.9% of refugees and 32.7% of host communities consuming sufficient Vitamin A-rich foods. However, a positive trend is emerging, as 69.6% of refugee households have embraced alternative livelihood strategies to complement government support, signalling a growing commitment to self-reliance and reducing dependency on external aid.